Association of obesity with television and other screen viewing, physical activity and food intake among elementary school children in Jeddah, Saudi Arabia - Bushra A Shojoon; Najlaa M Aljefree (International Journal of Food and Nutritional Health, 2026)
The prevalence of childhood obesity has greatly increased worldwide. Television viewing and other devices with screens are among contributing factors for obesity. This study included 282 elementary school children aged 6–13 years attending public and private schools in Jeddah. A self-administered online questionnaire distributed among the schools to collect data on sociodemographic characteristics, height, and weight, time spent on screens viewing, sleep duration and physical activity. The prevalence of overweight and obesity was 18.4% and 23.8%, respectively. Boys had a significantly higher risk of obesity (49.1%) than girls (37.6%) (P < 0.05). The majority of children had their own mobile phone (77.3%) and had their own tablet (56%). More than one-third of children spent 2–3 hours per day watching television and/or other devices. Children who played video games or watched videos 4 hours or more per day were more likely to be obese. Similarly, those who spent 4 hours or more per day using a mobile phone or tablet were more likely to be obese. Children who slept 6 hours or less were more likely to be obese. Children who exercised for 1 hour or less were less likely to be obese than those who never exercised. These findings call for the implementation of national programmes to reduce children’s use of electronic devices and improve lifestyle behaviours to reduce the prevalence of obesity among Saudi children.